Online labs to introduce undergraduate students to scientific concepts and practices in tree-ring research. Issue 1 (17th January 2022) - Davi, Nicole; Pringle, Patrick; Fiondella, Francesco; Lockwood, Jeff; Oelkers, Rose
Abstract: Scientists rely heavily on tree-ring records to better understand climate variability of the past millennium. Tree rings can also be utilized to give students a window into paleoclimate research, the methods scientists use, and the importance of scientific findings. Here, we present five online labs that introduce undergraduate students to the field of dendrochronology. Students learn about foundational tree-ring concepts and are guided to use many of the same tools and strategies as scientists, including exploring important field sites, measuring tree-ring data from those sites, using online paleoclimate databanks, and evaluating climate trends and extremes. The labs have been classroom tested and were modified based on a professional assessment, and faculty and student reviews. Faculty and student surveys and student lab grades show that the majority of students were able to meet the learning goals of the labs. Students reported that they felt they were working as scientists would, and, after completing the labs, that they better understood tree-ring science methods and applications. These materials were developed collaboratively with faculty input from a variety of institutions to have broad appeal and allow for use in a variety of classroom settings.